Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Characterization of Queen Supergene Pheromone in the Red Imported Fire Ant Using Worker Discrimination Assays - Haolin Zeng; Jocelyn G. Millar; Li Chen; Laurent Keller; Kenneth G. Ross (Journal of Chemical Ecology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Simple inheritance, complex regulation: Supergene‐mediated fire ant queen polymorphism - Samuel V. Arsenault; Joanie T. King; Sasha Kay; Kip D. Lacy; Kenneth G. Ross; Brendan G. Hunt (Molecular Ecology, 2020)
The fire ant Solenopsis invicta exists in two alternate social forms: monogyne nests contain a single reproductive queen and polygyne nests contain multiple reproductive queens. This colony‐level social polymorphism corresponds with individual differences in queen physiology, queen dispersal patterns and worker discrimination behaviours, all evidently regulated by an inversion‐based supergene that spans more than 13 Mb of a “social chromosome,” contains over 400 protein‐coding genes and rarely undergoes recombination. The specific mechanisms by which this supergene influences expression of the many distinctive features that characterize the alternate forms remain almost wholly unknown. To advance our understanding of these mechanisms, we explore the effects of social chromosome genotype and natal colony social form on gene expression in queens sampled as they embarked on nuptial flights, using RNA‐sequencing of brains and ovaries. We observe a large effect of natal social form, that is, of the social/developmental environment, on gene expression profiles, with similarly substantial effects of genotype, including: (a) supergene‐associated gene upregulation, (b) allele‐specific expression and (c) pronounced extra‐supergene trans ‐regulatory effects. These findings, along with observed spatial variation in differential and allele‐specific expression within the supergene region, highlight the complex gene regulatory landscape that emerged following divergence of the inversion‐mediated Sb haplotype from its homologue, which presumably largely retained the ancestral gene order. The distinctive supergene‐associated gene expression trajectories we document at the onset of a queen’s reproductive life expand the known record of relevant molecular correlates of a complex social polymorphism and point to putative genetic factors underpinning the alternate social syndromes.

Disruption of gene expression in hybrids of the fire ants Solenopsis invicta and Solenopsis richteri - LINO OMETTO; KENNETH G. ROSS; DeWAYNE SHOEMAKER; LAURENT KELLER (Molecular Ecology, 2012)
Transcriptome analysis is a powerful tool for unveiling the distribution and magnitude of genetic incompatibilities between hybridizing taxa. The nature of such incompatibilities is closely associated with the evolutionary histories of the parental species and may differ across tissues and between the sexes. In eusocial insects, the presence of castes that experience divergent selection regimes may result in additional distinct patterns of caste‐specific hybrid incompatibilities. We analysed levels of expression of >14 000 genes in two life stages of each caste in the fire ants Solenopsis invicta and Solenopsis richteri and in their hybrids. We found strong contributions of both developmental stage and caste to gene expression patterns. In contrast, variability in expression was only weakly associated with taxonomic identity, with hybrid scores falling between those of the two parental species. Hybrid incompatibilities were surprisingly modest, with only 32 genes being mis‐expressed, indicating low levels of disruption in gene regulation in hybrids; males and workers each mis‐expressed at least seven times as many genes as queens. Interestingly, homologues of many of the mis‐expressed genes have been implicated in behavioural variation in Drosophila melanogaster . General expression profiles of hybrids consistently were more similar to those of S. richteri than S. invicta , presumably because S. richteri trans ‐regulatory elements tend to be dominant and/or because there is an overall bias in the genetic composition of the hybrids towards S. richteri. Altogether, our results suggest that selection acting on each caste may contribute differently to interspecific divergence and speciation in this group of ants.

Venom Alkaloid and Cuticular Hydrocarbon Profiles Are Associated with Social Organization, Queen Fertility Status, and Queen Genotype in the Fire Ant Solenopsis invicta - Dorit Eliyahu; Kenneth G. Ross; Kevin L. Haight; Laurent Keller; Jürgen Liebig (Journal of Chemical Ecology, 2011)

A case study of human exacerbation of the invasive species problem: transport and establishment of polygyne fire ants in Tallahassee, Florida, USA - Joshua R. King; Walter R. Tschinkel; Kenneth G. Ross (Biological Invasions, 2009)

Putative native source of the invasive fire ant Solenopsis invicta in the USA - Eric J. Caldera; Kenneth G. Ross; Christopher J. DeHeer; D. DeWayne Shoemaker (Biological Invasions, 2008)

Experimental Conversion of Colony Social Organization in Fire Ants (Solenopsis invicta): Worker Genotype Manipulation in the Absence of Queen Effects - Dietrich Gotzek; Kenneth G. Ross (Journal of Insect Behavior, 2008)

Potential cause of lethality of an allele implicated in social evolution in fire ants - Brittan L. Hallar; Michael J. B. Krieger; Kenneth G. Ross (Genetica, 2007)

Species delimitation in native South American fire ants - KENNETH G. ROSS; D. DEWAYNE SHOEMAKER (Molecular Ecology, 2005)
The taxonomy of fire ants has been plagued by difficulties in recognizing species on the basis of morphological characters. We surveyed allozyme markers and sequences of the mtDNA COI gene in several closely related nominal species from two areas of sympatry in the native ranges to learn whether the morphology‐based delimitation of these species is supported by genetic data. We found that Solenopsis invicta and Solenopsis richteri , pest species whose distinctiveness has been debated, appear to be fully reproductively isolated at both study sites. This isolation contrasts with the extensive hybridization occurring between them in the USA, where both have been introduced. We also found strong genetic differentiation consistent with barriers to gene flow between Solenopsis quinquecuspis and the other two species. However, several lines of evidence suggest that nuclear and mitochondrial genes of S. invicta and S. richteri are introgressing into S. quinquecuspis . The latter apparently is a recently derived member of the clade that includes all three species, suggesting that there has been insufficient time for its full development of intrinsic isolating mechanisms. Finally, our discovery of genetically distinct populations within both S. invicta and S. richteri suggests the presence of previously unrecognized (cryptic) species. Their existence, together with the difficulties in developing diagnostic morphological characters for described species, imply that the group is actively radiating species and that morphological divergence generally does not keep pace with the development of reproductive isolation and neutral genetic divergence in this process.

Cladistic analysis of the fire ants of the Solenopsis saevissima species‐group (Hymenoptera: Formicidae) - James P. Pitts; Joseph V. McHugh; Kenneth G. Ross (Zoologica Scripta, 2005)
Results are presented from a phylogenetic study of the fire ants comprising the Solenopsis saevissima species‐group (Hymenoptera: Formicidae). Six most‐parsimonious trees were identified following a cladistic analysis utilizing 18 taxa and 36 morphological characters derived from three castes and two developmental stages. A strict consensus tree recovered the following relationships: ( S. daguerrei (( S. electra , S. pusilignis ) ( S. saevissima ( S. pythia ( S. interrupta , S. ‘undescribed species’ , S. weyrauchi ( S. richteri , S. invicta ( S. megergates ( S. quinquecuspis , S. macdonaghi )))))))). This phylogenetic hypothesis implies trends in fire ant evolution towards both polygyny (multiple egg‐laying queens per colony) and large major worker size. The phylogeny also provides a test of Emery's Rule, which is not supported in its strictest sense because the social parasite S. daguerrei is not the sister species to its host species. A modified version of Emery's Rule is supported, because the social parasite is the sister species to a larger clade containing its hosts, as well as nonhosts.

Effects of Wolbachia on mtDNA variation in two fire ant species - D. Dewayne Shoemaker; Gwen Keller; Kenneth G. Ross (Molecular Ecology, 2003)
Wolbachia are endosymbiotic bacteria that infect arthropods. As they are maternally transmitted, the spread of Wolbachia variants within host populations may affect host mtDNA evolution. We sequenced a portion of the mitochondrial cytochrome oxidase I gene from numerous individuals of two Wolbachia ‐infected fire ant species, Solenopsis invicta and S. richteri , to determine how these bacteria influence patterns of mtDNA variation. As predicted, there was a strong association between Wolbachia strain and host mtDNA lineage within and between these fire ant species. However, there was no consistent association between the presence of Wolbachia and a reduction in mtDNA diversity. Moreover, patterns of mtDNA variation within Wolbachia ‐infected populations did not differ consistently from neutral expectations, despite our prediction that strong positive selection acting on Wolbachia influences the evolutionary dynamics of other cytoplasmic genomes. Specifically, while values of Tajima's D consistently were less than zero for all six samples of fire ants harbouring Wolbachia , MacDonald–Kreitman tests suggested that the patterns of variation were different from those expected under neutrality in only two of the samples. We conclude that these neutrality tests do not unambiguously reveal a clear effect of Wolbachia infection on patterns of mtDNA variation and substitution in fire ants. Finally, consistent with an earlier study, our data revealed the presence of two divergent mtDNA haplotype lineages and Wolbachia strains within S. invicta . Recognition of these two lineages has important consequences for interpreting patterns of mtDNA evolution and genetic differentiation between conspecific social forms of this species.

Molecular ecology of social behaviour: analyses of breeding systems and genetic structure - Kenneth G. Ross (Molecular Ecology, 2001)
Molecular genetic studies of group kin composition and local genetic structure in social organisms are becoming increasingly common. A conceptual and mathematical framework that links attributes of the breeding system to group composition and genetic structure is presented here, and recent empirical studies are reviewed in the context of this framework. Breeding system properties, including the number of breeders in a social group, their genetic relatedness, and skew in their parentage, determine group composition and the distribution of genetic variation within and between social units. This group genetic structure in turn influences the opportunities for conflict and cooperation to evolve within groups and for selection to occur among groups or clusters of groups. Thus, molecular studies of social groups provide the starting point for analyses of the selective forces involved in social evolution, as well as for analyses of other fundamental evolutionary problems related to sex allocation, reproductive skew, life history evolution, and the nature of selection in hierarchically structured populations. The framework presented here provides a standard system for interpreting and integrating genetic and natural history data from social organisms for application to a broad range of evolutionary questions.

Unusual Behavior of Polygyne Fire Ant Queens on Nuptial Flights - Michael A. D. Goodisman; Christopher J. DeHeer; Kenneth G. Ross (Journal of Insect Behavior, 2000)

Lack of detectable nepotism in multiple-queen colonies of the fire ant Solenopsis invicta (Hymenoptera: Formicidae) - Christopher J. DeHeer; Kenneth G. Ross (Behavioral Ecology and Sociobiology, 1997)

Seasonal decline in intracolony genetic relatedness in eastern tent caterpillars: implications for social evolution - James T. Costa; Kenneth G. Ross (Behavioral Ecology and Sociobiology, 1993)

Diploid male production ? a significant colony mortality factor in the fire ant Solenopsis invicta (Hymenoptera: Formicidae) - Kenneth G. Ross; David J. C. Fletcher (Behavioral Ecology and Sociobiology, 1986)